2013
DOI: 10.18052/www.scipress.com/ilshs.19.217
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ICT in Teaching Science Education in Schools

Abstract: The place of ICT in teaching science education in schools cannot be over emphasized considering its promises in effective teaching and learning. This paper examine the role of ICT in teaching science education, its implication in both teaching and learning process and an attempt have been made to discuss the use of ICT in teaching and learning process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…Table 4 findings also present a good relationship between ICT adoption and students' academic performance, which is consistent with the study reported earlier of Iniesta-Bonillo et al [8]. e findings are also in congruence with those of other similar studies [14,16,17] that too claim that the adoption of ICT improves the quality of learning outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…Table 4 findings also present a good relationship between ICT adoption and students' academic performance, which is consistent with the study reported earlier of Iniesta-Bonillo et al [8]. e findings are also in congruence with those of other similar studies [14,16,17] that too claim that the adoption of ICT improves the quality of learning outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to the deterring factors mentioned above, Abdullahi (2014) has reported that the seeming reluctance on the part of many science teachers to integrate ICT-based teaching and learning activities into their everyday teaching may be linked to the unreliable and ineffective inhouse technological support that is common at many schools. Administrative hassles too, to access equipment and schedule times to use computer labs often frustrate teachers.…”
Section: Literaturementioning
confidence: 99%
“…Technology has allowed speeding up time via simulations of natural events; saving time through data collection devices and/or recording data that would otherwise be hard to gather; seeing things that could not otherwise be seen; organizing data that would otherwise be hard to organize; searching for information in databases; observing things that would otherwise be difficult to observe; and manipulating models of scientific phenomena (Abdullahi, 2014;Gerard, Varma, Corliss, & Linn, 2011;Juuti & Lavonen, 2012;Pow, Li, & Fung, 2008;Webb, 2005).…”
Section: Introductionmentioning
confidence: 99%